(untitled) (Journal of Computational Mathematics, 2021)
In this paper, a class of two-step continuity Runge-Kutta (TSCRK) methods for solving singular delay differential equations (DDEs) is presented. Analysis of numerical stability of the methods is given. We consider the two distinct cases: (i)τ ≥ h, (ii)τ < h, where the delay τ and step size h of the two-step continuity Runge-Kutta methods are both constant. The absolute stability regions of some methods are plotted and numerical examples show the efficiency of the method.